2017
DOI: 10.3390/geosciences7030080
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and Processing of Nadir and Stereo VHR Pleiadés Images for 3D Mapping and Planning the Land of Nineveh, Iraqi Kurdistan

Abstract: Abstract:The impressive hydraulic system built by the Assyrian King Sennacherib is composed by different archaeological areas, displaced along the Land of Nineveh, in Iraqi Kurdistan. The extensive project we are working on has the aim of mapping and geo-referencing any kind of documentation in order to design an archaeological-environmental park able to preserve and enhance the archaeological complex. Unfortunately, the area is failing a topographic documentation and the available cartography is not sufficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…For example, Malinverni et al [23] exploited stereo-pair processing of panchromatic and multispectral Pleiadés acquisitions with resolution of 0.5 and 2 m, respectively, to produce the first detailed topographic documentation of Khinis in Iraqi Kurdistan. Gupta et al [24], instead, used a 5 m grid spacing DEM generated from Cartosat-1 stereo pairs to locate archaeological mounds in the surroundings of the Buddhist site of Sannati in India and traced their elevation profiles.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Malinverni et al [23] exploited stereo-pair processing of panchromatic and multispectral Pleiadés acquisitions with resolution of 0.5 and 2 m, respectively, to produce the first detailed topographic documentation of Khinis in Iraqi Kurdistan. Gupta et al [24], instead, used a 5 m grid spacing DEM generated from Cartosat-1 stereo pairs to locate archaeological mounds in the surroundings of the Buddhist site of Sannati in India and traced their elevation profiles.…”
Section: Introductionmentioning
confidence: 99%
“…The capabilities of satellite remote sensing beyond site detection were proven by Borie et al [5] in a study that focused on the analysis of specific environmental resources. Malinverni et al [6] demonstrated the advantage of using remote sensing for the documentation of an archaeological complex that further served as support for perseveration and enhancement efforts. Satellite remote sensing plays a crucial role also in the condition assessment [7] and detection of threats to heritage sites [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Agapiou et al [8] 3278 1904 5 Agapiou et al [3] 1708 970 8 Chyla [9] 1429 827 1 Comer et al [5] 1570 1102 3 Corso et al [12] 1753 1215 2 Danti et al [10] 1943 1740 7 Drap et al [13] 1571 1565 2 Gade et al [6] 1751 1210 4 Garcia-Garcia et al [14] 1282 995 1 Guidi et al [15] 1719 976 3 Kalayci et al [16] 1218 968 2 Křivánek [17] 1420 1174 2 Malinverni et al [18] 1445 1345 1 Parcak et al [11] 1486 1374 3 Poux et al [19] 2306 2249 7 Rayne et al [7] 1750 1500 5 Rutishauser et al [4] 1784 1345 2 Sonnemann et al [20] 1582 1046 2 Tapete [1] 1256 2313 3 Traviglia & Torsello [2] 1680 1311 9 Verhoeven [21] 1573 1399 6 Building upon the positive outcome achieved in 2017 and in order to continue this Special Series, in March 2018 I launched the call for papers for a second edition of the Special Issue with the title "Earth Observation, Remote Sensing and Geoscientific Ground Investigations for Archaeological and Heritage Research".…”
Section: Authors Views Downloads Citationsmentioning
confidence: 99%